Investigation of social determinant of sustainable agrarian development - Todoruk, Sergy; Kutarenko, Nataliia; Kyfyak, Viktoria (Technology audit and production reserves, 2017)
The object of the investigation is a set of indicators that reflect the social component of the development of the agrarian sector of the national economy on the basis of sustainability. The main problems of social determinants can be determined by the analysis of a number of indicators. In particular, the level of employment in the agrarian sector is quite low, wages in agriculture are much lower than the average in Ukraine. The costs of social measures have the lowest weight in the cost structure of agricultural enterprises. Every year the number of rural population is rapidly decreasing, the situation with the birth rate in the countryside is similar. Today there are many villages in which there is no young generation, and only the population of retirement age is left. The level of development of social infrastructure is low. The article uses such general scientific methods as: – abstract-logical (for determining of the research structure), analysis and synthesis (in the analysis of key indicators); – dialectical (for the study of patterns of development and correlation of views, as well as phenomena and processes); – scientific abstraction (for focusing on the most significant aspects of the social development of the agrarian sector); – theoretical generalization (substantiation of directions of improvement of social determinants of sustainable agrarian development). Comparative and economic-statistical – in the process of analysis of trends in the development of elements of the social component of the agrarian sector and estimation of the level of social welfare of agricultural development in Ukraine. The investagation showed that the social determinants of sustainable development of the agrarian sector in Ukraine have an inadequate level of social security. It was concluded that Existing parameters need to be further developed and improved. It is necessary to improve the social climate in agrarian enterprises, in the sector as a whole. It is also necessary to improve the existing one and to develop a new social infrastructure, improvement of professional skills, pay levels and social guarantees of employees. This will enable to reduce social tensions, to stimulate the improvement of the quality of goods and services, and will motivate the further increase of productivity level. The mentioned combination will positively affect not only social but also other determinants of sustainable development of the agrarian sector of Ukrainian economy.